Membangun Loyalitas Pelanggan Melalui Promosi yang Efektif Studi Kasus Usaha Kebab di Wonokerto - Kartika Ramandhani; M. Taufiq Abadi (Universitas Katolik Widya Karya Malang, 2023)
This study aims to analyze how effective promotion can help build customer loyalty in kebab businesses in Wonokerto, and to find out whether the business is feasible or not to run. Qualitative case studies were conducted by conducting in-depth interviews with kebab business owners and several loyal customers, as well as observing promotional activities carried out. This study uses qualitative research methods to collect data and analyze complex phenomena in a specific language and cultural context. In-depth interviews were used to collect data from purposively selected informants, namely kebab business owners and some loyal customers. Observations were also made to obtain information regarding promotional activities carried out and interactions between customers and kebab business owners. The results of the study show that effective promotion can help build and maintain customer loyalty to kebab businesses in Wonokerto. Kebab business owners need to pay attention to customer needs and preferences in designing effective promotional strategies. Effective promotion must be able to attract customers and provide significant added value for them. Therefore, kebab business owners need to understand the characteristics of customers and the market environment to design targeted and effective promotional strategies. So that the business can be declared feasible to run.